A Requirement Model for School-Parent Online Communication System (SPOCS) - Noorfaizalfarid, Mohd Noor (2009)
The aim of this research is to develop a requirement model for School-Parent Online Communication System (SPOCS). SPOCS is required to help the parent to acquire their children information in school. Although there are some existing systems similar to SPOCS currently available in the market, the specifications and the features of these systems are different. Therefore, a requirement model will be constructed in this research to provide a generic model in developing a new SPOCS and to enhance the current system in the market. To construct the model, it has to identify and collect the requirements through a few fact-finding techniques and study on the existed systems. The constructed model has been used to develop the prototype of SPOCS. The acceptance of the prototype has been evaluated and tested by using Technology Acceptance Model (TAM). Findings for the evaluation process indicate that the constructed model is applicable to be used to develop SPOCS effectively and efficiently.